The Disruption of Retail Banking: A Competition Analysis of the Implications for Financial Stability and Monetary Policy. Issue 2 (10th September 2018) - Siciliani, Paolo
Abstract: This article analyses the competition impact of the implementation of two recent regulatory reforms aimed at boosting competition in retail banking by reducing consumer search and switching costs and empowering different business models whereby non-bank operators are able to compete with banks with respect to specific activities such as the provision of payment services. The article investigates how banks may react strategically in order to fend off the resulting competition threats which could undermine retail banks' reliance on the supply of sight retail deposits as their main source of funding. It also explores how financial regulators, in particular prudential authorities should respond, mindful of the risk for unintended consequences.